Primbon: Representation of Kraton Yogyakarta - Arfianti, Ami; Rachmawati, Murni; Setijanti, Purwanita (Interiority, 2022)
Primbon as Javanese local knowledge has been a guide for Javanese everyday and ritual life, included buildings, for decades. This paper intends to investigate the use of primbon in the Kraton Yogyakarta (Palace of Yogyakarta) as the representation of the sultan (king). The investigation was conducted through interpretive criticism to reveal the degree of conformity under the rules and principles in primbon as an attempt to form a new perspective in understanding the primbon.The analysis focuses on verses 172 and 194–196 of Primbon Betaljemur Adammakna, which deals with the arrangement of buildings. By transliterating the verses into English and interpreting the application of the verses in Kraton Yogyakarta, the study demonstrated the manifestation of theprimbon verses in the kraton’s building arrangement. The study of primbon reveals the role ofkraton as the representation of the earth in the universe, while the representation here displays the hierarchical arrangement of building facilities, from sacred to nonsacred or from private to public.